Using a Virtual Game System to Innovate Pulmonary Rehabilitation: Safety, Adherence and Enjoyment in Severe Chronic Obstructive Pulmonary Disease - Rima Wardini; Esther Dajczman; Nathan Yang; Marcel Baltzan; David Préfontaine; Maria Stathatos; Haguit Marciano; Shawn Watson; Norman Wolkove (Canadian Respiratory Journal)
OBJECTIVE: The present pilot study tested the use of a virtual game system (VGS) for exercise training in patients with moderate to very severe chronic obstructive pulmonary disease undergoing pulmonary rehabilitation (PR). Safety, feasibility, enjoyment and adherence were assessed.